Enhancing Coffee Farmers' Productivity through the Implementation of Huller Technology in Srigading Village - Ferdiansyah, Rifaldy; Imantaka, Farandy; Wibowo, Lisa Aprilia; Octavia, Devita Aliya; Deswara, Angger Bagas; Habbi, Muhammad Dimas; Ayuninda, Puput Tri (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study explores the impact of introducing huller machines to address productivity and quality challenges faced by coffee farmers in Srigading Village, Malang Regency, Indonesia. It aims to evaluate how modern technology can improve coffee processing and economic conditions for farmers. Method: The research involved providing and installing huller machines, followed by training and mentoring local farmers. Data was gathered through surveys and observations, assessing productivity and quality before and after implementation. Practical Application: The huller machines significantly improved processing efficiency, resulting in a 20% increase in productivity and a 15% reduction in coffee breakage. This led to a 25% rise in farmers' income. These improvements demonstrate how technological interventions can enhance agricultural practices and economic welfare in rural settings. Conclusion: The study confirms that huller technology effectively enhances coffee quality and productivity, offering a viable solution for similar agricultural challenges in other rural areas.